Sarcopenia Is Associated With Increased Risks of Rotator Cuff Tendon Diseases Among Community-Dwelling Elders: A Cross-Sectional Quantitative Ultrasound Study - Han, Der-Sheng; Wu, Wei-Ting; Hsu, Po-Cheng; Chang, Hsiang-Chi; Huang, Kuo-Chin; Chang, Ke-Vin (Frontiers in Medicine, 2021)
Backgrounds Recently, the association between sarcopenia and various musculoskeletal disorders, such as lumbar spine stenosis and fibromyalgia, has been highlighted. However, the relationship between sarcopenia and rotator cuff tendon diseases has rarely been investigated. This study aimed to evaluate whether sarcopenia was associated with shoulder pain and to determine whether rotator cuff tendons differed in echotexture between sarcopenic and non-sarcopenic populations. Methods The thickness and echogenicity ratio of the tendon versus the overlying muscle (ERTM) or subcutaneous tissue (ERTT) were measured using high-resolution ultrasonography in 56 sarcopenic patients and 56 sex- and age- matched controls. The association between ultrasound measurements of the rotator cuff tendon complex and sarcopenia was investigated using the generalized estimating equation (GEE). Results The sarcopenic group had an increased prevalence of shoulder pain. Based on the GEE analysis, sarcopenia was significantly associated with an increase in supraspinatus tendon thickness (β coefficient=0.447, p<0.001) and a decrease in the ERTM for the biceps log head and rotator cuff tendons. A negative trend of association was observed between sarcopenia and ERTT in the supraspinatus tendons (β coefficient=-0.097, p=0.070). Nevertheless, sarcopenia was not associated with an increased risk of rotator cuff tendon tears. Conclusions Patients with sarcopenia have a higher risk of shoulder pain. A consistent tendinopathic change develops in the supraspinatus tendons in sarcopenic patients. However, sarcopenia is less likely to be associated with serious rotator cuff pathology, such as tendon tears. Prospective cohort studies are warranted to explore the causal relationship between sarcopenia and shoulder disorders.